Adrenocortical Gap Junctions and Their Functions - Bell, Cheryl L.; Murray, Sandra A. (Frontiers in Endocrinology, 2016)
Adrenal cortical steroidogenesis and proliferation are thought to be modulated by gap junction-mediated direct cell-cell communication of regulatory molecules between cells. Such communication is regulated by the number of gap junction channels between contacting cells, the rate at which information flows between these channels and the rate of channel turnover. Knowledge of the factors regulating gap junction-mediated communication and the turnover process are critical to an understanding of adrenal cortical cell functions, including development, hormonal response to adrenocorticotropin (ACTH), and neoplastic de-differentiation. Here, we review what is known about gap junctions in the adrenal gland, with particular attention to their role in adrenocortical cell steroidogenesis and proliferation. Information and insight gained from electrophysiological, molecular biological and imaging (immunocytochemical, freeze fracture, transmission electron microscopic and live-cell) techniques will be provided.